2021
DOI: 10.21203/rs.3.rs-482279/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global, Regional, and National Burden of Kidney, Bladder, and Prostate Cancers and Their Attributable Risk Factors, 1990-2019

Abstract: Background: To investigate the burden and attributable risk factors for three genitourinary cancers in 204 countries and territories during 30 years.Methods: We extracted data of kidney, bladder, and prostate cancers from the Global Burden of Disease 2019 database, including incidence, mortality, disability-adjusted life-years (DALYs), and the attributable risk factors from 1990 to 2019. Estimated annual percentage changes (EAPC) were calculated to assess the changes in age-standardized incidence rate, age-sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…There are several factors that can contribute to delays in management of UBC including lack of awareness or knowledge from the public about disease symptoms, and delay in diagnostic testing and referral to specialists. [12][13][14][15] Socioeconomic and demographic factors, such as low-income and minority status, may also play a role in delay to treatment. 15 Therefore, SCP may be important to raise public awareness about the disease, improve education in the primary care units and implement systems to streamline the diagnostic and referral process for patients with suspected UBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several factors that can contribute to delays in management of UBC including lack of awareness or knowledge from the public about disease symptoms, and delay in diagnostic testing and referral to specialists. [12][13][14][15] Socioeconomic and demographic factors, such as low-income and minority status, may also play a role in delay to treatment. 15 Therefore, SCP may be important to raise public awareness about the disease, improve education in the primary care units and implement systems to streamline the diagnostic and referral process for patients with suspected UBC.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Socioeconomic and demographic factors, such as low-income and minority status, may also play a role in delay to treatment. 15 Therefore, SCP may be important to raise public awareness about the disease, improve education in the primary care units and implement systems to streamline the diagnostic and referral process for patients with suspected UBC. 7,9 On the other hand, a shorter time from referral to TURBT does not necessarily result in a shorter time to definitive treatment with, for example, cystectomy, 16,17 which emphasizes the importance of taking the entire process from symptom to definitive treatment into account.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the impact of socioeconomic status on the changing burden of kidney cancer [3][4] [5] . Recent research has shown that exposure to various risk factors has played a role in in uencing the prevalence of kidney cancer [6] .…”
Section: Introductionmentioning
confidence: 99%